Mitochondrial ferritin expression in human macrophages is facilitated by thrombin‐mediated cleavage under hypoxia. Issue 2 (1st December 2022) - Fuhrmann, Dominik C.; Becker, Sabrina; Brüne, Bernhard
Abstract : Ferritins are iron storage proteins, which maintain cellular iron homeostasis. Among these proteins, the ferritin heavy chain is well characterized, but the regulatory principles of mitochondrial ferritin (FTMT) remain elusive. FTMT appears to be cleaved from a 27 kDa to a 22 kDa form. In human macrophages, FTMT increased under hypoxia in a hypoxia‐inducible factor 2‐dependent manner. Occurrence of FTMT resulted from cleavage by thrombin, which was supplied by serum. Inhibition of thrombin as well as serum removal decreased FTMT, while supplementation of thrombin under serum‐deprived conditions restored its expression. Besides hypoxia, thrombin facilitated FTMT expression after treatment with the ferroptosis inducer RSL3 and the pro‐inflammatory stimulus lipopolysaccharide. This study provides insights into the regulation of FTMT under hypoxia and identifies thrombin as a FTMT maturation‐associated peptidase. Abstract : Hypoxia, via hypoxia‐inducible factor 2, induces the expression of mitochondrial ferritin (FTMT) in primary human macrophages. Here, we found that FTMT is cleaved to its active, ferroptosis‐antagonizing form by thrombin. Besides hypoxia, the ferroptosis inducer RSL3 and the pro‐inflammatory stimulus lipopolysaccharide also induce mature FTMT expression, which is prevented by blocking thrombin. Our findings imply a role for thrombin in protecting macrophages from ferroptosis.